1988
DOI: 10.1099/00221287-134-11-2977
|View full text |Cite
|
Sign up to set email alerts
|

Heterokaryon Incompatibility and Heterozygous Diploid Production in Tomato Wilt Isolates of Verticillium dahliae

Abstract: Auxotrophs derived by UV or N-methyl-N'-nitro-N-nitrosoguanidine mutagenesis from three North American, three European and four Australian tomato wilt isolates of Verticillium dahliae were used to investigate heterokaryon compatibility. Ninety 'crosses' involving race-1 and race-2 isolates were attempted using mixed conidial suspensions and a 'hanging drop' technique. Crosses between North American and Australian isolates failed to produce heterokaryons over a 20 d period but within each of these two groups of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0

Year Published

1993
1993
1999
1999

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…They reported that crossing between North American isolates and Australian isolates failed to produce heterokaryons, but the isolates were fully heterokaryon-compatible within each group, whereas European isolates showed variable compatibility with both the North American and Australian isolates. O'Garro and Clarkson (1988b) pointed out the homogeneity in the North American and Australian isolates and stated that race designation did not appear to affect compatibility. Results of vegetative compatibility among Japanese isolates of V. dahliae race-1 and race-2 also suggested the homogeneity of the Japanese isolates.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…They reported that crossing between North American isolates and Australian isolates failed to produce heterokaryons, but the isolates were fully heterokaryon-compatible within each group, whereas European isolates showed variable compatibility with both the North American and Australian isolates. O'Garro and Clarkson (1988b) pointed out the homogeneity in the North American and Australian isolates and stated that race designation did not appear to affect compatibility. Results of vegetative compatibility among Japanese isolates of V. dahliae race-1 and race-2 also suggested the homogeneity of the Japanese isolates.…”
Section: Discussionmentioning
confidence: 97%
“…O'Garro and Clarkson (1988b) studied the extent of heterokaryon incompatibility between V. dahliae race-1 and race-2 isolates from different geographical origins. They reported that crossing between North American isolates and Australian isolates failed to produce heterokaryons, but the isolates were fully heterokaryon-compatible within each group, whereas European isolates showed variable compatibility with both the North American and Australian isolates.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Heterokaryon compatibility groups suggested the existence of diverse genetic populations in imperfect fungi (6). It was examined by using complementary auxotrophic mutants (23,31) or color mutants (28). V. dahliae formed black microscletrotia where melanin granules concentrated in cell wall layers (36).…”
mentioning
confidence: 99%